2016
DOI: 10.1007/s00228-016-2110-5
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human study to assess guselkumab (anti-IL-23 mAb) pharmacokinetics/safety in healthy subjects and patients with moderate-to-severe psoriasis

Abstract: Guselkumab pharmacokinetic profiles were generally comparable between healthy subjects and patients with psoriasis. Guselkumab, administered as an IV infusion or SC injection, was well tolerated in healthy subjects and patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 18 publications
5
59
0
1
Order By: Relevance
“…The safety, efficacy and pharmacokinetic profile of guselkumab observed in this phase I study is consistent with that reported in the global phase I guselkumab psoriasis study . Further, the efficacy and safety up to 1 year in over 2000 patients in a phase II and two phase III studies of guselkumab in a moderate‐to‐severe psoriasis population have been reported .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The safety, efficacy and pharmacokinetic profile of guselkumab observed in this phase I study is consistent with that reported in the global phase I guselkumab psoriasis study . Further, the efficacy and safety up to 1 year in over 2000 patients in a phase II and two phase III studies of guselkumab in a moderate‐to‐severe psoriasis population have been reported .…”
Section: Discussionsupporting
confidence: 88%
“…). Dose selection was based on a previously conducted non‐Japanese phase I study . Dose escalation to sequential cohorts was guided by safety and tolerability data from previous dose cohorts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complete clearing is becoming a realistic expectation; 56·3% of patients treated with risankizumab sustained a PASI100 response at week 52 . The half‐life of tildrakizumab and risankizumab is 20–28 days; guselkumab's half‐life is 12–19 days . The far longer duration of pharmacological action supports a fundamental role for IL‐23 in psoriasis pathogenesis.…”
mentioning
confidence: 99%